Radiation Protocol for Three‐Dimensional Rotational Angiography to Limit Procedural Radiation Exposure in the Pediatric Cardiac Catheterization Lab. (14th April 2016) - Haddad, Lauren; Waller, B. Rush; Johnson, Jason; Choudhri, Asim; McGhee, Vera; Zurakowski, David; Kuhls‐Gilcrist, Andrew; Sathanandam, Shyam
Abstract: Background: Three‐dimensional rotational angiography (3DRA) offers more detailed anatomic information than 2D digital acquisition (2DDA). Concerns over potentially higher contrast and radiation doses have limited its routine use. Objective: The primary objective of this study was to compare radiation doses required to obtain 3DRA using a customized low dose radiation protocol with 2DDA. The secondary objective was to compare total procedural radiation in pediatric cardiac catheterization procedures utilizing 3DRA to those that do not. Study Design: Phantom studies were conducted to establish customized 3DRA protocols for radiation reduction. Comparison of 3DRA and non‐3DRA procedures in age‐, size‐ and diagnosis‐matched controls was performed. Radiation doses were indexed to body surface area (BSA) to account for differing body habitus as validated from the phantom study. Results: Study ( n  = 100) and control ( n  = 100) groups were matched for age (10.2 vs. 9.98 years; P  = .239) and BSA (1.23 vs. 1.09 m 2 ; P  = .103). The dose area product (DAP) to acquire a 3DRA was similar to a 5 s, 15 frames/second 2DDA (278 vs. 241 cGy/cm 2 ; P  = .14). Despite the 3DRA group consisting of more complex interventions, no difference was found in the total procedural Air Kerma and DAP indexed to BSA (244 vs. 249 mGy/m 2 ; P  = .79 and 3348 vs. 3176 cGy/cm 2 /m 2 ; P  = .48, respectively). The contrast volume to acquire a 3DRA compared to a 2DDA was greater (1.59 vs. 1.01 mL/kg; P  < .001). However, no difference was found for the entire procedure (3.8 vs. 4 mL/kg, P  = .494). This could have resulted from the need to obtain multiple 2DDAs to achieve the detail of a single 3DRA (11 vs. 7 per study; P  < .001). Conclusions: When 3DRA, using the proposed protocols is employed, total procedural contrast and radiation doses are comparable with the sole use of biplane cine‐angiograms. These protocols may allow for routine use of 3DRA for congenital cardiac catheterizations.